Effects of plyometric exercise on muscle soreness and plasma creatine kinase levels and its comparison with eccentric and concentric exercise - Jarmutas, A. Z.; Fatouros, I. G.; Buckenmeyer, P.; Kokkinidis, E.; Taxildaris, K.; Kambas, A.; Kyriazis, G. (The Journal of Strength and Conditioning Research, 2000)
The main purpose of this study was to examine the effects of plyometric exercise (P) on delayed onset of muscle soreness (DOMS) and plasma creatine kinase (CK) levels and compare them to the effects of eccentric (E) and concentric (C) exercises. A second purpose was to determine whether a repeated exercise session has similar effects on DOMS and CK in P compared to E and C. Subjects (n = 8 per group) were randomly assigned to P, E, or C groups. Subjects performed two exercise bouts separated by 6 weeks. Subjects in P performed six sets of drop and side jumps at 70% of their maximum jumping height, whereas those in E and C groups performed six sets of leg extensions and calf raises at 70% of their one repetition maximum (1RM). DOMS and CK were determined prior to and following each exercise session at 24, 48, and 72 hours postexercise. Repeated measures ANOVA showed that DOMS was significantly higher in P and E compared with C. There were no significant differences for CK between the three treatments. DOMS decreased significantly after the second exercise session (4.0 ± 0.6 vs. 2.6 ± 0.6) independent of treatment. CK also decreased significantly after the second session (649 ± 64.2 vs. 363 ± 37.2 IU·1L) independent of treatment. These results suggest that DOMS after an intense exercise session appears to be similar in P and E but lower in C. Furthermore, plasma CK responses after a P exercise session were similar to E and C exercises. Finally, a repeated exercise session, 6 weeks later after the first one, resulted in lower DOMS and CK values in all three groups.